Anthropometric Profile and Nutritional Status in Elderly: A Cross-Sectional Study (International Journal of Scientific Research and Management (IJSRM), 2021)
Background: Various screening tools are used to identify elderly individuals who are malnourished or at risk for malnutrition based on their nutritional status. Anthropometric measurements are important indicators of an individual’s nutritional status. In this study, we aimed to establish anthropometric standards for the Turkish elderly population and to investigate any significant relationship between anthropometric characteristics and nutritional status. Materials and Methods: Age, sex, weight, height, waist-to-hipratio (WHR) and body massindex (BMI) were recorded. We also administered the Mini Nutritional Assessment (MNA) and a hand grip test. Results: In our study, 72% of males and 84% of females were in the overweight group, 24% of males and 16% of females were in the normal weight group, and only 4% of males were in theweak group. For males, 76% were not at risk for malnutrition, 20% were at risk, and 4% were determined to have malnutrition. For females, 68% were not at risk for malnutrition, and 32% were at risk. There were no females who had malnutrition. With regard to muscle strength, 80% of males and 92% of females did not have sufficient strength. Weight, grip strength and WHR were significantly related to MNA (p < 0.05). Conclusion: We provided sex-specific distributions for many anthropometric measurements for the elderly which can be used as reference values for the Turkish elderly population to identify individuals at greater risk for nutritional disorders.